Dust bowl illustration - Thomas Hart Benton (artist):::Creator:::::::::::: (2024)
"A day went by and the wind increased, steady, unbroken by gusts." Illustration of a corn field in the drought of the Dust Bowl from vol.1 p.5 of The Grapes of Wrath illustrated edition, by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "During a night the wind raced faster over the land, dug cunningly among the rootlets of the corn, and the corn fought the wind with its weakened leaves until the roots were freed by the prying wind and then each stalk settled wearily sideways toward the earth and pointed the direction of the wind."